Improvement of the SAM algorithm based on causal structure analysis - Jia, Bin; Cai, Qingsong; Jia, Ming (Proceedings of SPIE, the international society for optical engineering, 2025)
In response to the computational complexity issue of the directed acyclic graph constraint in the Structure-Agnostic Model (SAM), we have proposed an innovative solution: an improved algorithm for the directed acyclic graph constraint based on continuous optimization. This algorithm, while maintaining the original acyclic constraint conditions, ingeniously introduces a hyperparameter α as an important component of the constraint. This improvement not only effectively reduces the computational complexity but also enhances the precision of the calculations to a certain extent.